2016
DOI: 10.1111/cxo.12361
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in laser in situ keratomileusis‐associated dry eye

Abstract: Dry eye is the most common complication after laser in situ keratomileusis (LASIK). The major cause of LASIK-associated dry eye is corneal nerve damage. Early identification and treatment of post-operative dry eye are essential to prevent further ocular surface damage. This article reviews the recent studies of LASIK-associated dry eye, including clinical features, aetiology, risk factors, evaluations and treatment. The applications of novel technologies in LASIK-associated dry eye evaluation like anterior seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 95 publications
(141 reference statements)
2
13
0
Order By: Relevance
“…Therefore, HD-OCT has the potential to become a routine eye evaluation method for DALK and other corneal surgeries. In our study, we found a significant negative correlation between age and CTFT in the fellow eye, which indicated that older age is a risk factor for tear film instability (Xie, 2016).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, HD-OCT has the potential to become a routine eye evaluation method for DALK and other corneal surgeries. In our study, we found a significant negative correlation between age and CTFT in the fellow eye, which indicated that older age is a risk factor for tear film instability (Xie, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…Dry eye is one of the common postoperative complications of corneal transplantation and may be associated with multiple mechanisms (Lin et al, 2014). During corneal-related surgery, the afferent nerve fibers of the cornea are severed, which may interrupt the cornea-trigeminal nerve-brainstem-facial nerve-lacrimal gland reflex arc and result in decreased tear secretion (Xie, 2016). The morphological changes of the transplanted cornea, such as corneal epithelium redistribution, the changed shape of the cornea and the sutures, may affect tear film distribution and increase tear evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, surgical incisions, conjunctival sutures and edema lead to morphological changes of ocular surface, which may also affect tear distribution and leading to decrease of tear film stability [27]. In this study, we found there were positive correlations between TMH and NITBUT-average at both 1 week and 2 weeks after PPV, demonstrating that surgery-induced reflex tearing also aggravates tear film destability.…”
Section: Discussionsupporting
confidence: 49%
“…The validation of new methods for the diagnosis of incipient cases of KC or with mild visual loss is of great interest in the field of ophthalmology since there are several clinical treatments that would permit the end of further development of the disease [23]. For this reason, this work tries to perform a morphological analysis of the corneal structure's response to both the linear decompensation and the annular profile defined in the singular points of corneal surfaces.…”
Section: Discussionmentioning
confidence: 99%